Analysis of the causes of diabetes mellitus occurrence in the chronic disease management program - Nur Sabriyah Latif; Andi Yusuf; Muhammad Khadafi S (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Chronic Disease Management Program (Prolanis) is a health service system carried out with a proactive approach whose implementation involves participants, health facilities and BPJS health for chronic disease sufferers. This study aimed to determine the factors that influence the incidence of Diabetes Mellitus in Prolanis Participants at the Pangkajene Health Center, Sidrap Regency. Research Methodology: The type of research used is Cross-Sectional Study research, which is a study where independent variables/causal factors/physical factors and dependent variables/consequential factors/effect factors are collected at the same time which was carried out at the Pangkajene Health Center, Sidrap Regency in the period March-April 2024 with a total of 68 participants. Result: The results of the study showed that the variables of age (ρ=0.031), obesity (ρ=0.002), diet (ρ=0.026), and genetic history (ρ=0.005) had an influence on the incidence of Diabetes Mellitus in Prolanis Participants at the Pangkajene Health Center, Sidrap Regency. Conclusion: The age variable is the variable that most influences the incidence of Diabetes Mellitus. There is a need for early detection in people who have a genetic history of diabetes mellitus and increasing community participation in Prolanis activities to be able to monitor degenerative diseases.